2013
DOI: 10.1017/s0952675713000195
|View full text |Cite
|
Sign up to set email alerts
|

The uniqueness of metrical structure: rhythmic phonotactics in Huariapano

Abstract: This article argues that, contrary to some recent proposals, a given phonological form may be organised into at most one array of metrical structure at a time. The bulk of the paper is dedicated to a case study of Huariapano, a language that has been claimed to motivate multiple, coexisting but autonomous, layers of metrical parsing. I show that this conclusion is premature : both stress and segmental patterning in Huariapano can be modelled within a single system of constituency, once context-dependent variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 73 publications
2
22
0
1
Order By: Relevance
“…On the other hand, unstressed syllables in other (non-foot-initial) metrical positions (i.e., σ 2 in (41)- (42)) seem to optionally allow /h/-deletion. These generalizations together tentatively confirm the foot-initial hypothesis of Bennett (2012Bennett ( , 2013 by which foot-initial weak syllables can be slightly stronger than other unstressed syllables, given the greater relative strength associated to prosodic-category-initial positions. In Dutch, as in English, the feature [spread glottis] surfaces foot-initially as a means of strengthening a privileged position.…”
Section: Licensing and Deletion Of The Glottal Fricative [H] In Dutchsupporting
confidence: 80%
See 4 more Smart Citations
“…On the other hand, unstressed syllables in other (non-foot-initial) metrical positions (i.e., σ 2 in (41)- (42)) seem to optionally allow /h/-deletion. These generalizations together tentatively confirm the foot-initial hypothesis of Bennett (2012Bennett ( , 2013 by which foot-initial weak syllables can be slightly stronger than other unstressed syllables, given the greater relative strength associated to prosodic-category-initial positions. In Dutch, as in English, the feature [spread glottis] surfaces foot-initially as a means of strengthening a privileged position.…”
Section: Licensing and Deletion Of The Glottal Fricative [H] In Dutchsupporting
confidence: 80%
“…This idea was already present in the analysis of several phonological distributions in other languages (see Kiparsky 1979;Withgott 1982;Jensen 2000;Davis and Cho 2003;Davis 2005;Harris 2013 on English;and Leer 1985;Rice 1992 on Chugach Alutiiq). It has been significantly reinforced in recent work by Bennett (2012Bennett ( , 2013, who demonstrated that even in iambic languages, foot-initial weak syllables (e.g., (σ ˈσ)) may undergo strengthening effects due to the greater relative prominence associated with prosodic-initial domains.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations